2012
DOI: 10.1371/journal.pone.0048331
|View full text |Cite
|
Sign up to set email alerts
|

Beaming into the Rat World: Enabling Real-Time Interaction between Rat and Human Each at Their Own Scale

Abstract: Immersive virtual reality (IVR) typically generates the illusion in participants that they are in the displayed virtual scene where they can experience and interact in events as if they were really happening. Teleoperator (TO) systems place people at a remote physical destination embodied as a robotic device, and where typically participants have the sensation of being at the destination, with the ability to interact with entities there. In this paper, we show how to combine IVR and TO to allow a new class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…For example, it is plausible to assume that in the future there will be many experiments combining real-time fMRI and VR or ones using animal subjects in VR (Normand et al, 2012), which are not only about understanding or improving VR itself but only use it a research tool. To begin with a short example, Behr et al (2005) have covered the research ethics of VR from a practical perspective, emphasizing that the risk of motion sickness must be minimized and that researchers ought to assist subjects as they leave the virtual environment and readjust to the real world.…”
Section: The Research Ethics Of Vrmentioning
confidence: 99%
“…For example, it is plausible to assume that in the future there will be many experiments combining real-time fMRI and VR or ones using animal subjects in VR (Normand et al, 2012), which are not only about understanding or improving VR itself but only use it a research tool. To begin with a short example, Behr et al (2005) have covered the research ethics of VR from a practical perspective, emphasizing that the risk of motion sickness must be minimized and that researchers ought to assist subjects as they leave the virtual environment and readjust to the real world.…”
Section: The Research Ethics Of Vrmentioning
confidence: 99%
“…The same kind of beaming setup has been used to create a shared environment between a small animal and a human. Normand et al (2012b) showed a human participant in VR interacting with a virtual human, which in fact was a tracked rat in a cage 12 km away. Simultaneously, the rat interacted with a ratsized robot, which in fact was moving determined by the tracked the movements of the remote human.…”
mentioning
confidence: 99%
“…In a recent experimental combination of 'immersive virtual reality' with 'teleoperator systems', an interdisciplinary team facilitated an equal-scale encounter between humans and rats. 40 The human subjects were immersed in a virtual reality environment, where their movements were monitored, and in turn drove the movement of a rat-shaped and -sized robotic device; the rat-robot was then placed next to a living rat, whose movements were translated into that of a human-sized avatar in the virtual environment. Thus levelled, it is claimed that the human and the rat were able to participate in a purportedly playful meeting of species that seems straight from the pages of science fiction.…”
Section: Interspecies Communicationmentioning
confidence: 99%